Kajian Hidrologi dan Analisis Kapasitas Pengaliran Penampang Sungai Way Kuripan terhadap Bencana Banjir Wilayah Bandar Lampung Berbasis Hec Ras - Hardiyanto, M. Agung; Amin, M.; Triyono, Sugeng; Ridwan, Ridwan (Jurnal Agricultural Biosystem Engineering, 2024)
This study aimed to determine flood height and also the area of flood in Way Kuripan River. The first step of this study is used hydrological analysis to obtain the maximum flow rate of Way Kuripan River a return periods of 2 years, 5 years, 10 years, 25 years, 50 years, and 100 years. Furthermore, to know capacities and water level of Way Kuripan River is required the hydraulic simulation process that is made easier by using Hydrologic Engineering Center-River Analysis System (HEC-RAS) program through 8 cross-sectional points. The HEC-RAS program can help be model the river flows in existing conditions with using steady flow options and input datas in the form of maximum discharge data. The output of the modeling using the HEC-RAS program can be seen in figure and tables form that present the characteristics of the Way Kuripan river cross section. The analysis of results of the HEC RAS with simulation till discharge plan when a return period of 100 years have been flood at 3 point cross section that is Sta. 4.6 and 7. In the cross section Sta. 6 has been flood as high as 1.94 meters on the right side. The flood areas include: Pesawahan, Kota Karang, Kuripan, Gedong Pakuon, Talang, Sukarame II, Negeri Olok Gading, Sumur Putri and Perwata. Keywords:  Flood, HEC RAS, Way Kuripan River.